The cognitive reflection test revisited: exploring the ways individuals solve the test. (3rd July 2017) - Szaszi, B.; Szollosi, A.; Palfi, B.; Aczel, B.
ABSTRACT: Individuals' propensity not to override the first answer that comes to mind is thought to be a crucial cause behind many failures in reasoning. In the present study, we aimed to explore the strategies used and the abilities employed when individuals solve the cognitive reflection test (CRT), the most widely used measure of this tendency. Alongside individual differences measures, protocol analysis was employed to unfold the steps of the reasoning process in solving the CRT. This exploration revealed that there are several ways people solve or fail the test. Importantly, 77% of the cases in which reasoners gave the correct final answer in our protocol analysis, they started their response with the correct answer or with a line of thought which led to the correct answer. We also found that 39% of the incorrect responders reflected on their first response. The findings indicate that the suppression of the first answer may not be the only crucial feature of reflectivity in the CRT and that the lack of relevant knowledge is a prominent cause of the reasoning errors. Additionally, we confirmed that the CRT is a multi-faceted construct: both numeracy and reflectivity account for performance. The results can help to better apprehend the "whys and whens" of the decision errors in heuristics and biases tasks and to further refine existing explanatory models.